Home page for accesible maths 9 Workshop Solutions

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

9.4 Workshop Solutions 4

W4.1. In both cases, the region of integration is as given in the following diagram:

xx

yy

11

22

11

(1,1)(1,1)

(1,2)(1,2)

We have

1201(yx3+y2ex)dxdy=12[yx44+y2ex]01dy\int_{1}^{2}\int_{0}^{1}(yx^{3}+y^{2}e^{x})\,dxdy=\int_{1}^{2}\Bigl[{{yx^{4}}% \over{4}}+y^{2}e^{x}\Bigr]_{0}^{1}\,dy
=12([y4+y2e]-[y2])dy=\int_{1}^{2}\Bigl(\Bigl[{{y}\over{4}}+y^{2}e\Bigr]-\Bigl[y^{2}\Bigr]\Bigr)dy
=12(y4+(e-1)y2)dy=\int_{1}^{2}\Bigl({{y}\over{4}}+(e-1)y^{2}\Bigr)\,dy
=[y28+(e-1)y33]12=\Bigl[{{y^{2}}\over{8}}+{{(e-1)y^{3}}\over{3}}\Bigr]_{1}^{2}
=[48+8(e-1)3]-[18+e-13]=\Bigl[{{4}\over{8}}+{{8(e-1)}\over{3}}\Bigr]-\Bigl[{{1}\over{8}}+{{e-1}\over{% 3}}\Bigr]
=38+7(e-1)3.={{3}\over{8}}+{{7(e-1)}\over{3}}.

Alternatively,

0112(yx3+y2ex)dydx=01[y2x32+y3e23]12dx\int_{0}^{1}\int_{1}^{2}(yx^{3}+y^{2}e^{x})\,dydx=\int_{0}^{1}\Bigl[{{y^{2}x^{% 3}}\over{2}}+{{y^{3}e^{2}}\over{3}}\Bigr]_{1}^{2}\,dx
=01([2x3+8ex3]-[x32+ex3])dx=\int_{0}^{1}\Bigl(\Bigl[{{2x^{3}+{{8e^{x}}\over{3}}}}\Bigr]-\Bigl[{{x^{3}}% \over{2}}+{{e^{x}}\over{3}}\Bigr]\Bigr)\,dx
=01(3x32+7ex3)dx=\int_{0}^{1}\Bigl({{3x^{3}}\over{2}}+{{7e^{x}}\over{3}}\Bigr)\,dx
=[3x48+7ex3]01=\Bigl[{{3x^{4}}\over{8}}+{{7e^{x}}\over{3}}\Bigr]_{0}^{1}
=38+7(e-1)3.={{3}\over{8}}+{{7(e-1)}\over{3}}.

W4.2. We have 0π6sec2(x+y)dx=[tan(x+y)]0π6=tan(y+π6)-tany\int_{0}^{\frac{\pi}{6}}\sec^{2}(x+y)\,dx=\left[\tan(x+y)\right]_{0}^{\frac{% \pi}{6}}=\tan(y+\frac{\pi}{6})-\tan y. For the next step,

0π6(tan(y+π6)-tany)dy=[log(cosy)-log(cos(y+π6))]0π6=log(cos2π6cos0cosπ3)=log32.\int_{0}^{\frac{\pi}{6}}(\tan(y+\frac{\pi}{6})-\tan y)\,dy=\left[\log(\cos y)-% \log(\cos(y+\frac{\pi}{6}))\right]_{0}^{\frac{\pi}{6}}=\log\left(\frac{\cos^{2% }\frac{\pi}{6}}{\cos 0\cos\frac{\pi}{3}}\right)=\log\frac{3}{2}.

W4.3. a) The auxiliary equation is s2+4s+3=(s+3)(s+1)s^{2}+4s+3=(s+3)(s+1), which has roots -3-3 and -1-1 (both single roots). Thus the general solution is y=Ae-3x+Be-xy=Ae^{-3x}+Be^{-x}.

b) The auxiliary equation is s2+4s+4=(s+2)2s^{2}+4s+4=(s+2)^{2}, which has a double root -2-2. Thus the general solution is y=(Ax+B)e-2xy=(Ax+B)e^{-2x}.

c) The auxiliary equation is s2+4s+5s^{2}+4s+5 which has complex roots -2±i-2\pm{\rm i}. Therefore the general solution is y=e-2x(Acosx+Bsinx)y=e^{-2x}(A\cos x+B\sin x).

W4.4. a) The auxiliary equation is s2-3s-4=(s-4)(s+1)s^{2}-3s-4=(s-4)(s+1), so the general solution is y(x)=Ae4x+Be-xy(x)=Ae^{4x}+Be^{-x}. For the initial value problem we have y(0)=1y(0)=1, so A+B=1A+B=1 and hence B=1-AB=1-A; since y(x)=4Ae4x-Be-xy^{\prime}(x)=4Ae^{4x}-Be^{-x} we have y(0)=4A-By^{\prime}(0)=4A-B, so substituting B=1-AB=1-A we obtain y(0)=5A-1y^{\prime}(0)=5A-1. Since y(0)=9y^{\prime}(0)=9 we have A=2A=2 and B=-1B=-1, hence y(x)=2e4x-e-xy(x)=2e^{4x}-e^{-x}.

b) Here the auxiliary equation is s2+2s+10s^{2}+2s+10 which has (strictly) complex roots -1±3i-1\pm 3{\rm i}. Hence the general solution to the equation is y(x)=e-x(Acos3x+Bsin3x)y(x)=e^{-x}(A\cos 3x+B\sin 3x). Since y(0)=0y(0)=0, we have A=0A=0, so y(x)=Be-xsin3xy(x)=Be^{-x}\sin 3x and we want to find the value of BB. Now y(x)=-Be-xsin3x+3Be-xcos3xy^{\prime}(x)=-Be^{-x}\sin 3x+3Be^{-x}\cos 3x, so y(0)=3By^{\prime}(0)=3B. Thus y(0)=1B=13y^{\prime}(0)=1\;\Rightarrow B=\frac{1}{3}, so the solution is y(x)=13e-xsin3xy(x)=\frac{1}{3}e^{-x}\sin 3x.

W4.5. We divide both sides through by (x+1)(x+1) to obtain dydx=x+2x+1\frac{dy}{dx}=\frac{x+2}{x+1}, which we can solve by integrating. Then x+2x+1=1+1x+1\frac{x+2}{x+1}=1+\frac{1}{x+1}, so the solution is y=x+log|x+1|+cy=x+\log|x+1|+c.

W4.6. This is an integrable equation, so to solve it we have to divide through by (x3+x-2)2(x^{3}+x-2)^{2} so that it has the form dydx=q(x)\frac{dy}{dx}=q(x). Then we obtain dydx=3x2+1(x3+x-2)2\frac{dy}{dx}=\frac{3x^{2}+1}{(x^{3}+x-2)^{2}}. Fortunately we don’t have to do much work to integrate the right-hand side, since it is of the form f(x)f(x)2\frac{f^{\prime}(x)}{f(x)^{2}} where f(x)=x3+x-2f(x)=x^{3}+x-2. Hence, after integrating, we obtain the general solution y=-1x3+x-2+cy=\frac{-1}{x^{3}+x-2}+c. For the particular solution with y(0)=32y(0)=\frac{3}{2}, we have c+12=32c+\frac{1}{2}=\frac{3}{2}, so c=1c=1. Hence the solution to the initial-value problem is y=1-1x3+x-2y=1-\frac{1}{x^{3}+x-2}.

(*) The denominator x3+x-2x^{3}+x-2 has a real root x=1x=1, and it factorizes as (x-1)(x2+x+2)(x-1)(x^{2}+x+2). The quadratic x2+x+2x^{2}+x+2 is irreducible (with complex roots -1±-32\frac{-1\pm\sqrt{-3}}{2}), so x3+x-2x^{3}+x-2 is non-zero on the range x<1x<1. Since we define the initial value at x=0x=0, this means that the maximum possible region on which the solution is valid is the set of all x<1x<1.

W4.7. To solve this equation we divide through by yy to obtain

1ydydx=x2+1dyy=(x2+1)dx\frac{1}{y}\frac{dy}{dx}=x^{2}+1\;\;\Rightarrow\int\frac{dy}{y}=\int(x^{2}+1)% \,dx

and hence log|y|=x33+x+c\log|y|=\frac{x^{3}}{3}+x+c. To get this into the form y=f(x)y=f(x) we take the exponential on both sides to obtain y=Aex3/3+xy=Ae^{x^{3}/3+x} where AA is a constant. Clearly y(0)=Ay(0)=A, so the particular solution with y(0)=3y(0)=3 is y=3ex3/3+xy=3e^{x^{3}/3+x}.

W4.8 This is a separable differential equation, so we can solve it by multiplying through by 3(y+1)23(y+1)^{2} to obtain 3(y+1)2dy=xdx\int 3(y+1)^{2}\,dy=\int x\,dx, so that (y+1)3=x22+c(y+1)^{3}=\frac{x^{2}}{2}+c. Taking cube roots, we obtain y+1=x22+c3y+1=\sqrt[3]{\frac{x^{2}}{2}+c} and hence the general solution to the equation is y=-1+x22+c3y=-1+\sqrt[3]{\frac{x^{2}}{2}+c}.

W4.9. We first divide through by (x3+1)(x^{3}+1) so that the equation is in the standard form, to obtain: dydx-3x2x3+1y=x2x3+1\frac{dy}{dx}-\frac{3x^{2}}{x^{3}+1}y=\frac{x^{2}}{x^{3}+1}. Now we determine the integrating factor I(x)=eF(x)I(x)=e^{F(x)} where F(x)=-3x2x3+1dxF(x)=\int\frac{-3x^{2}}{x^{3}+1}\,dx. We find F(x)F(x) by substituting u=x3+1u=x^{3}+1, so that we obtain -duu=-logu=-log(x3+1)\int\frac{-du}{u}=-\log u=-\log(x^{3}+1). Hence I(x)=e-log(x3+1)=1x3+1I(x)=e^{-\log(x^{3}+1)}=\frac{1}{x^{3}+1}. Multiplying through by I(x)I(x), we obtain the integrable equation

1x3+1dydx-3x2(x3+1)2=ddx(yx3+1)=x2(x3+1)2.\frac{1}{x^{3}+1}\frac{dy}{dx}-\frac{3x^{2}}{(x^{3}+1)^{2}}=\frac{d}{dx}\left(% \frac{y}{x^{3}+1}\right)=\frac{x^{2}}{(x^{3}+1)^{2}}.

Integrating both sides, and observing that the right-hand side is f(x)3f(x)\frac{f^{\prime}(x)}{3f(x)} where f(x)=x3+1f(x)=x^{3}+1, we find the general solution:

yx3+1=-13(x3+1)+cy=c(x3+1)-13.\frac{y}{x^{3}+1}=-\frac{1}{3(x^{3}+1)}+c\;\;\Rightarrow y=c(x^{3}+1)-\frac{1}% {3}.

For the particular solution with y(0)=1y(0)=1, we have c-13=1c-\frac{1}{3}=1 and hence c=43c=\frac{4}{3}. Thus the solution to the initial-value problem is y=43x3+1y=\frac{4}{3}x^{3}+1.

W4.10. We divide through by 2 and transfer the yy term to the left-hand side to obtain dydx-(tanx)y=x\frac{dy}{dx}-(\tan x)y=x. To solve this we need to multiply by the integrating factor, which is eF(x)e^{F(x)} where F(x)=(-tanx)dxF(x)=\int(-\tan x)\,dx. To find F(x)F(x) we observe that (-tanx)dx=-sinxdxcosx\int(-\tan x)\,dx=\int\frac{-\sin x\,dx}{\cos x} and the derivative of denominator (cosx\cos x) is the numerator (-sinx-\sin x), so this integral is log|cosx|\log|\cos x|. (Alternatively we make the substitution u=cosxu=\cos x to get the same result.) Hence the integrating factor is I(x)=cosxI(x)=\cos x.

Multiplying through by I(x)I(x), the equation becomes (cosx)dydx-(sinx)y=xcosx(\cos x)\frac{dy}{dx}-(\sin x)y=x\cos x where the left-hand side is ddx(ycosx)\frac{d}{dx}\left(y\cos x\right). Thus we have ycosx=xcosxdx=xsinx-sinxdx=xsinx+cosx+cy\cos x=\int x\cos x\,dx=x\sin x-\int\sin x\,dx=x\sin x+\cos x+c, where we integrated by parts in the second equality. Thus the general solution of the equation is y=xtanx+1+csecxy=x\tan x+1+c\sec x.